Investigation of concealed objects detection in visible, infrared and terahertz ranges of radiation - Kowalski, Marcin; Kastek, Mariusz; Palka, Norbert; Polakowski, Henryk; Szustakowski, Mieczyslaw; Piszczek, Marek (Photonics Letters of Poland, 2013)
One of the most crucial social issues is assuring the safety of crowded public places like e.g. airports. One aspect of this problem is the detection of potentially dangerous objects hidden under person’s clothing. There are various solutions to find different suspicious elements: from simple metal detectors up to X-ray scanners. Moreover, some of available solutions are harmful to human beings. Therefore, there is a great potential in using multispectral surveillance imagers in security systems and that is why we investigate the possibilities of concealed object detection by screening people using non-invasive cameras working in various spectral ranges. Full Text: PDF References C. Jansen et al., "Terahertz imaging: applications and perspectives", Appl. Optics 19, 49 (2010). CrossRef M.C. Kemp, "Millimetre wave and terahertz technology for the detection of concealed threats: a review", Proc. SPIE 6402, 64020D (2006). CrossRef E. Grossman et al., "Passive terahertz camera for standoff security screening", Appl. Optics 19, 49 (2010). CrossRef L. Yun-Shik, Principles of Terahertz Science and Technology (Springer 2008). CrossRef X. Zhang, J. Xu, Introduction to THz Wave Photonics (Springer 2010). CrossRef B.B. Hu, M.C. Nuss, "Imaging with terahertz waves", Opt. Lett. 20, 16 (1995). CrossRef M. Piszczek, M. Kowalski, M. Szustakowski, "Measurement Stand for TeraEYE Inspection", Acta Phys. Pol. A 4, 120 (2011). DirectLink M. Kastek et al., "Multispectral and hyperspectral measurements of soldier's camouflage equipment", Proc. SPIE 8382, 83820K (2012). CrossRef M. Kastek et al., "Method of gas detection applied to infrared hyperspectral sensor", Phot. Lett. Poland 4, 4 (2012). CrossRef http://www.digitalbarriers.com/products/thruvision/ DirectLink M. Kastek, T. Piątkowski, P. Trzaskawka, "Infrared imaging fourier transform spectrometer as the stand-off gas detection system", Metrology and Measurement Sys. 18, 4 (2011). DirectLink M. Kowalski, N. Palka, M. Piszczek, M. Szustakowski, "Hidden Object Detection System Based on Fusion of THz and VIS Images", Acta Phys. Pol. A 124, 3 (2013). CrossRef M. Kowalski, N. Palka, M. Piszczek, M. Szustakowski, "Processing of THz images acquired by passive camera", Phot. Lett. Poland 4, 3 (2012). CrossRef M. Kowalski, N. Palka, M. Piszczek, M. Szustakowski, "The methodology of THz-VIS fused images evaluation", Phot. Lett. Poland 5, 1 (2013). CrossRef